THE EFFECTIVENESS OF SCAFFOLDING TECHNIQUE TO IMPROVE READING COMPREHENSION IN NARRATIVE TEXT FOR EIGHTH GRADERS OF SMPN 43 SURABAYA Selmi - SELMI, (RETAIN : Journal of Research in English Language Teaching, 2015)
Abstrak Membaca adalah salah satu skil yang harus dikuasai oleh siswa. Akan tetapi, di dalam kelas membaca, terutama membaca narrative text, siswa kurang motivasi dan merasa jenuh. Akibatnya, mereka kesulitan memahami teks yang mereka baca. Untuk mengatasi masalah ini, peneliti perlu menggunakan pemahaman membaca yang dapat memotivasi siswa untuk meningkatkan kemampuan membaca. Dalam hal ini, peneliti dapat menggunakan sebuah teknik yang dinamakan Scaffolding. Penelitian ini dirancang untuk mengetahui keefektifan teknik scaffolding untuk menigkatkan pemahaman membaca teks naratif kepada siswa kelas delapan. Pokok permasalahan dalam penelitian ini adalah “ apakah ada signifikan perbedaan pada kemampuan siswa membaca naratif teks diantara siswa yang diajarkan menggunakan scaffolding dan yang diajarkan tanpa menggunakan scaffolding? Dalam melakukan penelitian, peneliti menggunakan eksperimental quantitatif dengan mengumpulkan data melalui pemberian pretes, pemberian dua tritmen, kemudian pemberian postes setelah tritmen untuk mendapatkan nilai siswa di dalam tritmen. Tetapi, sebelum pretes dilaksanakan, peneliti memberikan sebuah percobaan kepada kelas lain tidak untuk kelas yang mana dipilih sebagai eksperimen dan kontrol grup. Percobaan ini dilakukan untuk mengetahui apakah tes bisa menjadi tes yang baik atau tidak sebelum diberikan sebagai pretes dan postes. Ada dua variabel dalam penelitian ini. Penggunaan teknikscaffolding dipilihsebagai variabelindependen danpemahamanmembaca siswaadalah variabeldependendaripenelitian ini.Populasinya adalahsiswa kelasdelapan SMPNegeri43dansampelpenelitian ini adalahdua kelasyangdipilihsecara tidak acaksebagai kelompokkontroldankelompok eksperimen. Untukinstrumenadalahtesdanuji coba. Penelitimenganalisissecara kuantitatifdengan menggunakant-test untuk mengetahuiperbedaan yang signifikandalam penguasaan membacaantara kelas delapanyangdiajarkanmenggunakanscaffoldingdalam teksnaratif danmereka yang tidak. Penelitimenemukan bahwaskorkelompok eksperimen(80,00) dankelompok kontrol(72,75). Ini berartibahwa adamaknayang berbedadalam penguasaan membacaantarasiswa kelasdelapanyangdiajarkanmenggunakanscaffoldingdalam teksnaratif danmereka yang tidak. Siswamendapatkankemajuanyang tinggikarena merekamendapatkan tritmen menggunakan teknikscaffolding. Penguasaanmembacamerekameningkat danjuga membuat merekamendapatkanskor yang lebih tinggidari sebelumnya. Berdasarkanhasil penelitian, teknikscaffolding cocok digunakanuntuk mengajarkan pemahaman membaca dalam teksnaratifuntukkelasdelapandalam meningkatkankemampuan membacamereka. Kata Kunci:Teknik Scaffolding, PemahamanMembaca, TeksNaratif. Abstract Reading is one of four skills that students have to master. However, in reading class, especially reading of narrative text the students lack of motivation and get bored. As a result, they feel difficult to comprehend the text they read. To solve this problem, the researcher needs to use reading comprehension which can motivate the students to improve their reading ability. Due to the need, the researcher can use a technique named Scaffolding. This research is designed to know the effectiveness of scaffolding technique to improve reading comprehension in narrative text to the eighth graders. The point of this research is on “Is there any significant difference in the students’ reading ability of narrative text between the students who taught by using scaffolding and those who are taught without using scaffolding? In conducting the research, the researcher used an experimental quantitative by collecting the data through giving pretest, giving two treatments, then giving posttest after treatment to get the students’ score in treatment. But, before pretest was held, the researcher gave a tryout to other class not for classes which were chosen as experimental and control group. This tryout was done to know whether the test could be the good test or not before it was given as pretest and posttest. There were two variables in this research. The use of scaffolding technique were chosen as independent variable and students’ reading comprehension were dependent variables of this research. The population was the eighth graders of SMP Negeri 43 and the samples of this research were two classes which were chosen not randomly as an experimental group and control group. For the instruments were test and tryout. The researcher analyzed quantitatively by using t-test to find out the significant difference in reading mastery between eight graders who are taught using scaffolding in narrative text and those who are not. The researcher found that the score of experimental group (80.00) and Control group (72.75). It means that there was significance different in reading mastery between the eighth graders who are taught using scaffolding in narrative text and those who are not. The students’ get high progress since they got treatment using scaffolding technique. Their reading mastery was increased and also make them get higher score than before. Based on the result of the research, scaffolding technique is appropriate to be used to teach reading comprehension in narrative text to the eight graders to improve their reading ability. Key Words: Scaffolding Technique, Reading Comprehension, Narrative Text